Aspekty etyczne badań naukowych w polskim pielęgniarstwie - Kunecka, Danuta (Annales. Etyka w Życiu Gospodarczym, 2015)
Recent years in Poland have been characterized by the dynamic development of scientific activity among nurses. It might have been caused by several factors, namely: the rising needs and expectations of representatives of this professional group, the necessity of adjusting to EU standards, changes in the system of education, as well as the individual “research needs” of those representatives. However, is there a correlation between the increase in the quantity of scientific research and its quality? An attempt to answer that question led the author to formulate this paper’s goal, which had been formulated as follows: to analyse different sources of information concerning the reality of scientific research in nursing in Poland.